Antioxidant activity and inhibition of key enzymes linked to type-2 diabetes and hypertension by azadirachta indica-yogurt - Shori, A.B.; Baba, A.S.H. (2011)
Azadirachta indica is widely used in traditional medicine to treat diabetes and hypertension. In the present study A. indica-yogurt was prepared and refrigerated up to 28 days. pH of A. indica-yogurt was lower whereas total titratable acid (TTA) was higher than plain-yogurt during storage. The total phenolic content (TPC) and antioxidant capacity increased during storage. A. indica-yogurt had highest TPC (74.9 ± 5.1 μgGAE/ml; p < 0.05) on day 28 and DPPH inhibition (53.1 ± 5.0%; p < 0.05) on day 14 compared to plain-yogurt (29.6 ± 1.1 μgGAE/ml and 35.9 ± 5.2%, respectively). The OPA values increased between day 7 and 21 of storage but reduced on the 4th week of storage with values for A. indica-yogurt being higher (p < 0.05) than plain-yogurts. Maximum inhibition of α-amylase (47.4 ± 5.8%), α-glucosidase (15.2 ± 2.5%) and angiotensin-1 converting enzyme (ACE, 48.4 ± 7.2%) by plain-yogurt water extract occurred on day 7, 14 and 0, respectively. A. indica-yogurt water extract increased the inhibition to maximal values for α-glucosidase and ACE on day 14 of storage (15.9 ± 10.1% and 79.70 ± 11.2%, respectively) and for α-amylase on day 21 of storage (54.8 ± 3.2%). A. indica-yogurt has higher TPC, antioxidant activities and enzymes inhibitory effects than plain-yogurt. Thus A. indica-yogurt may have the potential to serve as enhanced functional yogurt with anti-diabetic and anti-hypertension activities. © 2011.